2020
DOI: 10.1099/mgen.0.000417
|View full text |Cite
|
Sign up to set email alerts
|

Accurate quantification of bacterial abundance in metagenomic DNAs accounting for variable DNA integrity levels

Abstract: The quantification of the total microbial content in metagenomic samples is critical for investigating the interplay between the microbiome and its host, as well as for assessing the accuracy and precision of the relative microbial composition which can be strongly biased in low microbial biomass samples. In the present study, we demonstrate that digital droplet PCR (ddPCR) can provide accurate quantification of the total copy number of the 16S rRNA gene, the gene usually exploited for assessing total bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…To verify the significance of the results, 24 specimens were prepared by dividing each sample into eight identical sampling tubes. We confirmed the integrity (e.g., DNA degradation, concentration, and purity) of the extracted microbial genomic DNA by considering the extraction of high-quality metagenomic DNA may affect its accurate microbial quantification 24 . In the case of the LoopSeq 16S Microbiome SSC 24-Plex kit, it consisted of a multiplex workflow that pools at least 24 samples into a single tube per sequencing run, thus, we performed the 16S V3–V4 amplicon sequencing procedure with the same samples.…”
Section: Resultssupporting
confidence: 55%
“…To verify the significance of the results, 24 specimens were prepared by dividing each sample into eight identical sampling tubes. We confirmed the integrity (e.g., DNA degradation, concentration, and purity) of the extracted microbial genomic DNA by considering the extraction of high-quality metagenomic DNA may affect its accurate microbial quantification 24 . In the case of the LoopSeq 16S Microbiome SSC 24-Plex kit, it consisted of a multiplex workflow that pools at least 24 samples into a single tube per sequencing run, thus, we performed the 16S V3–V4 amplicon sequencing procedure with the same samples.…”
Section: Resultssupporting
confidence: 55%
“…The presence of chlorine is known to negatively affect planktonic bacteria’s growth in DWDSs [ 18 , 51 ]. In terms of the quality of extracted DNA, gel electrophoresis ( S1 Fig ) shows the prominent absence of intact DNA, indicating low DNA integrity caused by degradation [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A rarefaction curve is also useful to assess whether the maximum sample diversity has been achieved and down amplification to lower reads (e.g., 10-100 reads/gene copies) is justifiable. However, low DNA concentration or any genetic markers have been demonstrated to give high false-negative results, increased false discovery and artefactual results [44,52] that is likely to be the case for sequencing-based studies in chlorinated drinking water [29]. We found that many reported drinking water microbiome studies from chlorinated systems (including 16s rRNA amplicon sequencing/ metabarcoding, metagenomics) [20,[56][57][58][59][60][61][62][63][64] often exclude raw experimental data of extracted DNA concentrations that is crucial to assess the quality of the sequencing results.…”
Section: No Impact Of Water Volume On Dna Recoverymentioning
confidence: 99%
“…Digital PCR was performed to determine the total number of 16S copies by using universal primers targeting the V5–V6 regions of 16S rDNA (primer sequences: forward, B-V5□:□5′-ATTAGATACCCYGGTAGTCC-3′; reverse, A-V6, 5′-ACGAGCTGACGACARCCATG-3′), according to established procedures (52).…”
Section: Methodsmentioning
confidence: 99%
“…Digital PCR was performed to determine the total number of 16S copies by using universal primers targeting the V5-V6 regions of 16S rDNA (primer sequences: forward, B-V5 : 5′-ATTAGATACCCYGGTAGTCC-3′; reverse, A-V6, 5′-ACGAGCTGACGACARCCATG-3′), according to established procedures (52). Absolute quantification was performed using QuantaSoft version 7.4.1 software (Bio-Rad, Hercules, CA, USA,) and the negative/positive thresholds were set manually, excluding samples with a number of droplets <10 000.…”
Section: Ddpcr Experimentsmentioning
confidence: 99%